THE INFLUENCE OF JOB TRAINING, CAREER PATH CERTAINTY AND COMPENSATION ON CONTRACT EMPLOYEE LOYALTY AT PT. ABAD JAYA GROUP ACEH - Bambang Gunawan; Prihatin Lumbanraja; Anizar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
One of the benchmarks of a company's success is human resources. Human resources are considered important because they can affect the efficiency and effectiveness of the company, and are the company's main expenses in carrying out its activities. Humans always play an active role in every company activity, namely as planners, actors and determinants of the realization of company goals, thus making humans a company asset that must be maintained, its efficiency and productivity improved. Saying that employee work loyalty is the determination and ability to follow with full awareness, responsibility, determination and ability that must be shown in daily attitudes and behavior, and in carrying out tasks. This opinion is interpreted that employee loyalty to work arises internally and loyalty to the company where they work because of their responsibility and ability. This research approach is quantitative research. Quantitative research methods can be interpreted as methods used to research a particular population or sample, data collection using research instruments, statistical data analysis, with the aim of testing the established hypothesis. While this type of research uses associative research. Associative research is research that aims to determine the relationship between two or more variables.